NEW ASPECTS OF DEFORMED CROSS-STRATA IN FLUVIAL SANDSTONES: EXAMPLES FROM NEOPROTEROZOIC FORMATIONS IN NORTHERN NORWAY - Røe S.-L.; Hermansen M. (My University, 2006)
Extensive (20–200 m long) exposures of tabular cross-sets in Neoproterozoic fluvial sandstone in Northern Norway demonstrate that deformed cross-strata, in the form of recumbently folded cross-strata with associated massive sand, are localized features passing in both up- and down-current direction into undeformed, concave-upward or sigmoidal cross-strata. The deformation occurs in down-current inclined, tangential wedge-shaped zones beneath reactivation surfaces, and less commonly as flat-topped lenticular zones. The localized nature of the sediment deformation is attributed to local liquefaction below the top of the bed in the case of the flat-topped lenses and at the dune front in the case of the more common tangential wedges. The position of the flat-topped lenses suggests deformation by the shear stress of high-velocity, suspension-laden currents. Although liquefaction of the dune front implies the action of gravity forces, it is argued that the fluvial currents were the main driving force at the instant of bed liquefaction. Post-folding gravitational shearing probably enhanced the deformation within the upper part of the wedges, with their long, flat-lying toeset resulting from redeposition of downslope-moving liquefied sand.
Keywords: Neoproterozoic; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская